2019
DOI: 10.1371/journal.pone.0218040
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea alters hematological, biochemical and inflammatory biomarkers in Brazilian children with SCA: Investigating associations with βS haplotype and α-thalassemia

Abstract: This study investigated the effects of hydroxyurea (HU) on hematological, biochemical and inflammatory parameters in children with sickle cell anemia (SCA) in association with β S haplotype and α-thalassemia. We included 22 children with SCA who were followed for an average of 14.5 months. Laboratory parameters were assessed by electronic methods, and molecular analysis was investigated by PCR-RFLP and allele-specific PCR. Results showed significant increases in hemoglobin, HbF, hematocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
3
8
0
Order By: Relevance
“…These findings corroborate previous studies, which also demonstrated improvements in hemolytic, hepatic and inflammatory profiles in patients with SCA undergoing HU therapy ( de Souza Santos and Maia, 2010 ; Voskaridou et al, 2010 ; de Souza Torres et al, 2012 ; Pallis et al, 2014 ; Belini Junior et al, 2015 ; Shome et al, 2016 ; Quarmyne et al, 2017 ; Colombatti et al, 2018 ). We further observed an increase in HDL-C concentration, demonstrating the effect of HU on lipid metabolism, which is consistent with our previous results ( Yahouédéhou et al, 2018b ; Yahouédéhou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings corroborate previous studies, which also demonstrated improvements in hemolytic, hepatic and inflammatory profiles in patients with SCA undergoing HU therapy ( de Souza Santos and Maia, 2010 ; Voskaridou et al, 2010 ; de Souza Torres et al, 2012 ; Pallis et al, 2014 ; Belini Junior et al, 2015 ; Shome et al, 2016 ; Quarmyne et al, 2017 ; Colombatti et al, 2018 ). We further observed an increase in HDL-C concentration, demonstrating the effect of HU on lipid metabolism, which is consistent with our previous results ( Yahouédéhou et al, 2018b ; Yahouédéhou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…These findings corroborate previous studies, which also demonstrated improvements in hemolytic, hepatic and inflammatory profiles in patients with SCA undergoing HU therapy (de Souza Santos and Maia, 2010;Voskaridou et al, 2010;de Souza Torres et al, 2012;Pallis et al, 2014;Belini Junior et al, 2015;Shome et al, 2016;Quarmyne et al, 2017;Colombatti et al, 2018). We further observed an increase in HDL-C concentration, demonstrating the effect of HU on lipid metabolism, which is consistent with our previous results (Yahouedehou et al, 2018b;Yahouedehou et al, 2019). The present analysis of genotype and/or allele distribution of rs2740574, rs3892097, and rs7943316 revealed frequencies divergent to those observed in other studies conducted in different patient populations, as well as healthy controls (Maruf et al, 2012;Sayed and Imam, 2012;Liu et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is in keeping with analysis from the MSH 37 and BABY‐HUG 38 studies, although other smaller studies have reported contrasting findings 36 . In keeping with a recent publication, 60 we also demonstrated that treatment with HU precipitated a fall in MCHC, and that this was still seen in those with α‐thalassemia despite the lower baseline MCHC. This likely represents an important therapeutic effect of HU in addition to its primary effect of raising the HbF%.…”
Section: Discussionsupporting
confidence: 92%